Enzymatic Characteristics of In-Vitro Incorporation of P32 Orthophosphate into Human Platelet Phosphatide - Grossman, C. M; Kohn, R (Thrombosis and Haemostasis, 1965)
The incorporation of P32 orthophosphate into phosphatide by isolated human platelets in an artificial medium was studied. The addition of homologous plasma increased the incorporation and the formation of labelled phosphatide was significantly reduced in the absence of oxygen or in the presence of cyanide, and by varying the pH from 7.4 to 5.6 and 8.6. The enzymatic character of the incorporation and the role of platelet respiration are briefly discussed.